Information needs regarding the national animal identification system in the livestock auction market industry - K. Bolte; Kevin C. Dhuyvetter; Ted C. Schroeder (Kansas Agricultural Experiment Station Research Reports, 2008)
The National Animal Identification System (NAIS) is a federal-level voluntary program that uses a streamlined information system designed to help animal health officials and producers respond to animal health threats in a timely manner.2 Electronic individual animal identification systems likely will be the popular choice among cattle producers who adopt individual animal identification systems. Because auction markets are the first market for many cattle, livestock markets are a natural place to implement animal identification scanning and recording. Therefore, it is important to understand livestock market operators' knowledge, concerns, views, and adoption of the NAIS and electronic animal identification systems. If livestock market operators do not understand the NAIS or animal identification systems they might misconstrue or misunderstand information on these systems. In addition, it is important to identify livestock market operators' concerns about electronic animal identification systems so issues can be addressed.
Keywords: Cattlemen' s Day; 2008; Kansas Agricultural Experiment Station contribution; no. 08-212-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 995; Beef; Cattle; National Animal Identification System (NAIS)